Mona Lisa smile [videorecording (DVD)] - Newell, Mike, 1942-; Roberts, Julia, 1967-; Dunst, Kirsten, 1982-; Stiles, Julia, 1981-; Gyllenhaal, Maggie, 1977- (Columbia TriStar Home Entertainment, 2004)
Set in 1953, Katherine Watson is a free-spirited graduate of UCLA who accepts a teaching post at Wellesley College, a women-only school where the students are torn between the repressive mores of the time and their longing for intellectual freedom.